Analisis Efisiensi Energi dan Material di Pabrik Gula Tradisional Menggunakan Pendekatan Berbasis STEM - Kurniawan, Muhammad Prasetya; Destia Maharani, Ara; Putri Pradita, Sintia; Daffa Nurramdhana, Almaira; Aulia Mahardini Gunawan, Citra; Anggraini Larasati, Errika (Jurnal Ilmiah Inovasi, 2024)
Traditional sugar factories face challenges in improving production efficiency to remain competitive and meet growing market demand. This research adopts an innovative STEM (Science, Technology, Engineering, and Mathematics) approach to analyze material and energy flows in the sugar production process. This approach not only identifies inefficiencies but also offers data-driven solutions and modern technology for operational optimization. The research involved material and energy flow mapping using the mass and energy balance method, along with causal analysis to identify the root causes of inefficiencies at each stage of production, from preparation, milling, refining, to crystallization. The results showed a production yield of 6,63%, far below the company's target of 10%, with the main inefficiencies caused by low raw material quality, non-standard process temperature settings, and inadequate operator skills. STEM-based recommendations include integrating sensor technology for real-time monitoring, regular machine maintenance using predictive algorithms, creating digital guidelines for operators, and optimizing raw materials through agronomic data. Implementing this approach is expected to improve yield and production efficiency and support operational sustainability by reducing waste and emissions.